Pulmonary Cement Embolism following Percutaneous Vertebroplasty - Ümran Toru; Tuba Coşkun; Murat Acat; Hilal Onaran; Şule Gül; Erdoğan Çetinkaya (Case Reports in Pulmonology)
Percutaneous vertebroplasty is a minimal invasive procedure that is applied for the treatment of osteoporotic vertebral fractures. During vertebroplasty, the leakage of bone cement outside the vertebral body leads to pulmonary cement embolism, which is a serious complication of this procedure. Here we report a 48-year-old man who was admitted to our hospital with dyspnea after percutaneous vertebroplasty and diagnosed as pulmonary cement embolism.